Evaluasi Kinerja dan Prioritas Penanganan Bangunan Irigasi pada Daerah Irigasi (DI) Beringin, Kecamatan Wajak - Kiki Frida Sulistyani; Suhudi Suhudi; Eva Rusdyana Wirasanti (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2025)
This study aims to evaluate the physical and functional performance of infrastructure and determine management priorities in the Beringin Irrigation Area (DI), Wajak District, which serves 131 hectares of agricultural land. Decreased performance of irrigation networks caused by sedimentation conditions and existing damage. The method used is a quantitative approach through a survey of infrastructure inventory in each irrigation network segment. Performance evaluation is carried out based on the Irrigation System Performance Index standard, which includes assessment of the physical condition and function of the building. The infrastructure of DI Beringin as a whole includes the main building (intake), carrier channels, complementary buildings, sewers, and inspection roads. The results of the study showed variations in conditions in each infrastructure component. The main building shows optimal performance with a value of 81% (Good/Routine Maintenance category). On the other hand, complementary buildings recorded the lowest value of 60.59% which indicates the category of Moderately Damaged and requires handling in the form of rehabilitation. These findings confirm that although the infrastructure is still complete in its existence, a priority management strategy is needed to prevent further degradation of function. The priority of the treatment produced is the rehabilitation of complementary buildings and sewers. Periodic maintenance for Carrier Lines and routine maintenance for main buildings and inspection roads. Medium handling priority for complementary buildings and sewer lines and low for carrier lines. The results of this study are expected to be recommendations for irrigation managers in determining the scale of maintenance priorities so that the distribution of water to agricultural land is maintained in a sustainable manner.